Circuits and Systems Issues in Power Electronics Penetrated Power Grid - Tse, Chi K.; Huang, Meng; Zhang, Xi; Liu, Dong; Li, Xiaolu Lucia (IEEE open journal of circuits and systems, 2020)
The penetration of power electronics into power generation and distribution systems has deepened in recent years, as prompted by the increasing use of renewable sources, the quest for higher performance in the control of power conversion, as well as the increasing influence of economic plans that necessitate power trading among different regions or clusters of power distribution. As a result of the increased use of power electronics for controlling power flows in power systems, interactions of power electronics systems and conventional synchronous machines' dynamics would inevitably cause stability and robustness concerns, which can be readily understood by the coupling effects among interacting dynamical systems of varying stability margins (or transient performances). In this article, we present the various problems of power electronics penetration into power grids and the implications on the stability and robustness of power networks. We specifically attempt to bring together two distinct perspectives, namely, bottom-up (local) and top-down (global) perspectives, and examine the current progress and future direction of research in power systems amidst the extensive deployment of power electronics.